Hyperbaric vs. isobaric bupivacaine for spinal anaesthesia for elective caesarean section: a Cochrane systematic review. (17th October 2017) - Sng, B. L.; Han, N. L. R.; Leong, W. L.; Sultana, R.; Siddiqui, F. J.; Assam, P. N.; Chan, E. S.; Tan, K. H.; Sia, A. T.
Summary: Both isobaric and hyperbaric bupivacaine have been used for spinal anaesthesia for elective caesarean section, but it is not clear if one is better than the other. The primary objective of this systematic review was to determine the effectiveness and safety of hyperbaric bupivacaine compared with isobaric bupivacaine administered during spinal anaesthesia for elective caesarean section. We included 10 studies with 614 subjects in the analysis. There was no evidence of differences either in the risk of conversion to general anaesthesia, with a relative risk (95%CI) of 0.33 (0.09–1.17) (very low quality of evidence), or in the need for supplemental analgesia, the relative risk (95%CI) being 0.61 (0.26–1.41) (very low quality of evidence). There was also no evidence of a difference in the use of ephedrine, the amount of ephedrine used, nausea and vomiting, or headache. Hyperbaric bupivacaine took less time to reach a sensory block height of T4, with a mean difference (95%CI) of −1.06 min (−1.80 to −0.31). Due to the rarity of some outcomes, dose variability, use of adjuvant drugs and spinal technique used, future clinical trials should look into using adequate sample size to investigate the primary outcome of the need for supplemental analgesia.